1973
DOI: 10.1136/hrt.35.10.1085
|View full text |Cite
|
Sign up to set email alerts
|

Subvalvular left ventricular aneurysms. A report of 5 Ugandan cases.

Abstract: The pathological features of 5 cases of subvalvular cardiac aneurysms occurring in Uganda over a 13-year period are described; 3 were subaortic and 2 were submitral. One of the latter was atypical in that the aneurysm arose at some distance below thefibrous mitral ring and was associated with endomyocardialfibrosis. In 2 cases where the coronary sinus and its ostium was examined, no abnormality was detected.Previous descriptions of the pathological aspects ofsubvalvular aneurysms are briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

1976
1976
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 6 publications
0
16
0
2
Order By: Relevance
“…Subaortic left ventricular aneursyms are seen very infrequently and the reported cases in the medical literature are from Africa and India [1][2][3][4]. This interesting patient is the first case of subaortic left ventricular aneurysm reported from Turkey.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Subaortic left ventricular aneursyms are seen very infrequently and the reported cases in the medical literature are from Africa and India [1][2][3][4]. This interesting patient is the first case of subaortic left ventricular aneurysm reported from Turkey.…”
Section: Discussionmentioning
confidence: 78%
“…Most of the reported cases were from Africa and India [1][2][3][4]. Although subaortic left ventricular aneuysm are usually congenital, it has been reported that they can be developed due to infection or trauma [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The aneurysm presently described occurs almost exclusively in blacks and is encountered primarily among Nigerians and South African Bantus [3,[5][6][7][8][9][10][11][12][13][14][16][17][18][19]. However, isolated reports ofthese aneurysms in blacks from the United States and the West Indies have been published [1, 2,4,12,15].…”
Section: Discussionmentioning
confidence: 99%
“…Case 1 still maintains good functional capacity and Case 2 has compensated well after treatment for congestive heart failure. However, in spite ofthe high mortality figures for surgical resection of these aneurysms (Abrahams et al, 1962;Chesler et al, 1965;Poltera and Jones, 1973) surgery will be considered as soon as progressive deterioration takes place in either patient.…”
Section: Commentsmentioning
confidence: 99%
“…Aneurysm of the left ventricle occurring in young people is considered to be a rare condition (Abrahams et al, 1962) and has been described mainly in Nigeria, South Africa, and Uganda (Abrahams et al, 1962;Chesler et al, 1965;Poltera and Jones, 1973). These aneurysms are usually submitral or subaortic, the former being more frequent (Abrahams et al, 1962;Cockshott et al, 1967).…”
mentioning
confidence: 99%